Expansion of Activated Lymphocytes Obtained from Renal Cell Carcinoma in an Automated Hollow Fiber Bioreactor - Gilda G. Hillman Ph.D.; Martin L. Wolf; Emily Montecillo; Elia Younes; Esa Ali; J. Edson Pontes; Gabriel P. Haas (Cell Transplantation, 1994)
Immunotherapy using IL-2 alone or combined with activated lymphocytes has been promising for metastatic renal cell carcinoma. Cytotoxic lymphocytes can be isolated from tumors, expanded in vitro with IL-2, and adoptively transferred back into the tumor-bearing host. These cells can also be transduced with the genes coding for cytokines for local delivery to tumor sites. A major drawback in adoptive immunotherapy is the cumbersome and expensive culture technology associated with the growth of large numbers of cells required for their therapeutic effect. To reduce the cost, resources, and manpower, we have developed the methodology for lymphocyte activation and expansion in the automated hollow fiber bioreactor IMMUNO*STAR™ Cell Expander (ACT BIOMEDICAL, INC). Tumor Infiltrating Lymphocytes (TIL) isolated from human renal cell carcinoma tumor specimens were inoculated at a number of 108 cells in a small bioreactor of 30 ml extracapillary space volume. We have determined the medium flow rates and culture conditions to obtain a significant and repeated expansion of TIL at weekly intervals. The lymphocytes cultured in the bioreactor demonstrated the same phenotype and cytotoxic activity as those expanded in parallel in tissue culture plates. Lymphocyte expansion in the hollow fiber bioreactor required lower volumes of medium, human serum, IL-2 and minimal labor. This technology may facilitate the use of adoptive immunotherapy for the treatment of refractory malignancies.